Cross‐coupling over frequency and sequence in impedance modelling of grid‐connected inverter. Issue 13 (19th December 2017) - Xu, Yunyang; Nian, Heng; Xu, Guodong; Qiu, Jixing
Abstract : Impedance‐based stability theory is an effective technique in grid‐inverter system stability analysis. In existed research based on this theory, sequence impedance models are assumed to have linear behaviour under small‐signal operation, and the grid‐inverter system can be decoupled into positive‐ and negative‐sequence subsystems. However, this may lead to wrong conclusions if there is cross‐coupling over frequency and sequence, which can be caused by phase locking loop (PLL), asymmetric current regulators, and soft dc bus. Here, the cross‐coupling will be analysed, and a 2 × 2 analytical admittance matrix model of grid‐connected inverter will be derived and validated, which can describe the cross‐coupling caused by PLL and asymmetric current regulators. The influence of the cross‐coupling on system stability is also discussed.